IDENTIFIKASI POTENSI DAN HAMBATAN PENGEMBANGAN TANAMAN TORBANGUN (Coleus amboinicus L) - Damanik, Kevin Aditya; Hasibuan, Syahbudin; Candra, Ifan Aulia (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2025)
Coleus amboinicus, known locally as torbangun, is a shrub from the Lamiaceae family that has thick stems, hairy green leaves, and a distinctive aroma. This plant is widely used in traditional medicine for various purposes, including increasing breast milk production and treating digestive disorders. C. amboinicus has great potential in developing pharmaceutical and nutraceutical products thanks to its active phytochemical content such as flavonoids, phenolics and essential oils. The potential for research development lies in further exploration of the bioactive contents of this plant and the mechanisms of its therapeutic action. Some examples of developments that can be carried out include clinical research regarding the effectiveness of torbangun in antimicrobial therapy, anticancer and immunomodulatory effects. In addition, optimization of extraction methods and more efficient identification of bioactive components are also potential areas for further research. However, the development of C. amboinicus also faces several obstacles, including a lack of clinical data supporting the safety of long-term use as well as obstacles in mass cultivation outside its natural habitat. More in-depth research is needed to overcome these challenges, especially in aspects of agronomy, biotechnology, and product formulation that meets modern pharmaceutical standard